Non-linear relationship between control ownership and cumulative abnormal return: A new predictive tool for firms’ performance - Zandi, Gholamreza; Rahman, Nik Khadijah Nik Abdul; Shahzad, Imran Ahmed; Choo, Sandy Low Bee (Nurture, 2023)
Purpose: The primary aim of the paper was to find out the non-linear relationship between ownership structure and the Cumulative Abnormal Return (CAR) of companies listed on the Muscat Stock Exchange (MSE) from 2013 to 2020. Design/Methodology/Approach: The Cumulative Abnormal Return (CAR) has been implied to determine the accuracy and ability of investors to predict stock performance and select an investment basket. Findings: The effect of Control Ownership (CO) on Cumulative Abnormal Return (CAR) of Muscat Stock Exchange (MSE) listed companies is negative which indicates that with increasing Control Ownership (CO) of stock, stock returns will fluctuate and Cumulative Abnormal Return (CAR) will decrease. Moreover, the results of the research show that the effect of Control Ownership Squared (CO2) on the Cumulative Abnormal Return (CAR) of Muscat Stock Exchange (MSE) listed companies is positive. Conclusion: The effect of the Herfindahl-Hirschman Index including institutional ownership, the Board of Directors (BOD) and the volume of stock exchanges is significant on the Cumulative Abnormal Return (CAR) of companies listed on the Muscat Stock Exchange (MSE). Practical Implications and Contribution to Literature: This research indicates that by increasing Control Ownership (CO) of the stock, the fluctuations of stocks’ returns and the Cumulative Abnormal Return (CAR) of Muscat Stock Exchange (MSE) listed companies will primarily decrease but the increase in CO will increase the volatility of the corporation’s Cumulative Abnormal Return (CAR). In fact, it was claimed that the relationship between CO and CAR is similar to a U-shaped parabola.